Plasticization of the ocean - Schröder, Solveig (2015)
Marine litter is a recently emerging environmental problem. It originates from the careless and inaccurate handling of production, consumption and treatment of (plastic) products which ultimately become litter and threaten both the marine ecosystem and humans depending on a healthy ocean. This research is based on the assumption that marine litter lies at the crossroad between humans’ relation to litter and their relation to nature. A frame analysis of the marine litter discourse in major German newspapers was conducted which is based on the premise of social constructivism and symbolic interactionism: that meaning is constructed through interaction (also with text) in which language plays an important role. The aim was to identify how the marine litter problem, the responsibilities and the individual’s role are constructed within the frames. This should provide a glimpse of the marine litter discourse in German newspapers from which individuals construct meaning and understanding of the marine litter problem. The frame analysis of 37 articles from five major German newspapers has revealed that the problem is framed with a focus on litter, without necessarily setting it in the context of the complex social and natural systems in which this problem is embedded. Nature-litter relations are on the forefront of the frames, such as describing a plasticized ocean which has become a threat. The marine natural system, humans and also society play a secondary role within the frames and are mainly seen in connection to litter, but not to each other. While the individual is largely framed as a consumer, it is argued that this enhances the agency of the individual, but also places much of the responsibility on him/her. Furthermore, the frames suggest that humans are neither part of society nor the natural system which complicates the issue of human-nature relations and responsibilities that are at the core of the marine litter problem, as it is argued in this research. This has lead to the assumption that it is a common responsibility for the natural environment, as well as the social system, which would be crucial to establish in order to overcome the problem of marine litter. However, this is not fostered within the frames found in this analysis.